ChemInform Abstract: A Multistep Flow Process for the Synthesis of Highly Functionalized Benzoxazoles. Issue 11 (18th March 2014) - Sedelmeier, Joerg; Lima, Fabio; Litzler, Alain; Martin, Benjamin; Venturoni, Francesco
Abstract Treatment of substrates (I) with BuLi under continuous flow conditions allows to minimize the hold‐up time for the resulting unstable lithiated benzoxazole intermediates which react with various electrophiles to give the corresponding substituted benzoxazoles.